Empowerment and waste management as a program to boost the economic condition in Geduang Village - Kurnia, Marlina; Fadlil, Andi Maufal; Karlina, RR Lina; Khasanah, Fatimah Nurul; Juniyati, Gita; Saraswati, Febriana Dewi (Community Empowerment, 2021)
The purpose of this service activity is to change the mindset of the community to implement a waste bank system as a solution for handling waste in Geduang Village, Kalijoso Payaman, Secang District. The method used to achieve this goal is to disseminate information about waste banks and waste processing to target groups, establish a waste bank organization, and implement waste bank management. The stages of activities carried out include preparation, socialization, implementation of training, formation of associations, and evaluation. The results achieved in addition to increasing awareness for the community about the importance of processing waste properly and correctly, also the success of the community in making new handicraft products through waste media that has economic value.